A case report: incidental diagnosis of endometrial tuberculosis in cases of abnormal uterine bleeding - B. V., Induja; Sawant, Vasudha; Potdar, Mohan; Dalvi, Rupali Mahesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Abnormal uterine bleeding (AUB), including heavy menstrual bleeding (HMB), levy a massive burden on society. Here, we discuss about two patients who came to OPD with AUB symptoms for evaluation, but incidentally diagnosed with endometrial tuberculosis. In Case 1, 45-year-old female came with complains of heavy menstrual bleeding for 6 months for 6 months. USG showed adenomyosis. Patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy. But on day 7 she developed serous blood-tinged discharge per vaginum. Incidentally, patient endometrial CBNAAT report came positive for MTB, with no resistance to rifampicin. Patient was started on anti-tubercular treatment for 6 months. In Case 2, 43-year-old female came with complaints of HMB with pain abdomen and irregular menses for 3 years. USG shows early changes of Adenomyosis. Patient underwent therapeutic curettage with MIRENA insertion. Endometrial CBNAAT was negative and liquid culture (LJ) was MDR positive. Sensitivity report s/o of isoniazid and rifampicin resistant. Patient was advised monthly close follow up as symptoms were under control. When a routine screening for FGTB by CBNAAT is done for cases of AUB, there are high chances of reporting more cases in a developing nation like India. Hence sending endometrial samples for TB screening in AUB cases can be useful in finding out more cases of genital TB, where their symptoms can be related to TB infection rather than searching for a structural cause that may be is not the cause for the severe symptoms. Due to which mismanagement or unnecessary surgical interventions can be avoided.